Increased Growth and Yield of Peanuts (Arachis Hypogaea L.) with Tillage and Liquid Organic Fertilizer Fish Waste. - Ardian Ardian; Sri Yoseva; Aan Pasbama Sinaga Naibaho; Angga Pramana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Peanut (Arachis hypogaea L.) is an important food commodity in Indonesia. The low production of peanuts in Riau Province has not been able to meet the people's need for peanuts. According to the Riau Province Food Crops Service (2022) the need for peanuts in Riau Province in 2019 is 8,516 tons, in 2020 the need for peanuts is 7,390 tons, and in 2021 the need for peanuts is 6,474 tons. This study aims to determine the effect and interaction between tillage and the application of fish waste liquid organic fertilizer (POC) and the single factor of both the growth and production of peanut plants and to get the best combination. The research was conducted using a split-plot design. The first factor as the main plot is tillage consisting of three levels, namely without tillage, minimum tillage, and maximum tillage. The second factor as a subplot was POC concentration consisting of four levels, without POC fish waste, 25% POC fish waste (250 ml POC + 750 ml water), 50% POC fish waste (500 ml POC + 500 ml water), and 50 % POC waste fish 75% (POC 750 ml + water 250 ml). Parameters observed included plant height, number of primary branches, flowering age, harvest age, number of pods, number of filled pods, seed production per plant, and weight of 100 seeds. The data obtained were analyzed statistically using analysis of variance and continued with Duncan's multiple range test at the 5% level using the SAS application. The results showed that the interaction of tillage and POC fish waste affected increasing plant height, number of primary branches, number of pods, number of filled pods, seed production per plant, and weight of 100 seeds.